Developing Critical Thinking Through HOTS-Based Authentic Assessment in Economics: Mengembangkan Berpikir Kritis Melalui Penilaian Autentik Berbasis HOTS di Bidang Ekonomi - Jupri, Tomi Jupri; Tinus, Agus; Wurianto, Arif Budi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the era of the Merdeka Curriculum, authentic assessment has become pivotal in promoting real-world application of knowledge. Specific Background: Particularly in economics education, developing critical thinking is essential due to the complexity of economic phenomena. Knowledge Gap: While existing research explores either authentic assessment or Higher Order Thinking Skills (HOTS), studies rarely integrate both within a specific subject context at the secondary level. Aims: This study aims to analyze the planning, implementation, and impact of HOTS-based authentic assessments on students’ critical thinking skills in economics. Results: Employing a descriptive qualitative method involving teachers and students at SMAN 1 Gerung, the findings indicate that while the cognitive aspects of assessment are systematically planned and implemented, the affective and psychomotor domains remain underdeveloped due to time and technical constraints. Novelty: This research introduces a context-sensitive assessment model tailored to economics education, incorporating HOTS indicators (C3–C5) and addressing local classroom challenges. Implications: The study provides practical guidance for educators to design assessments that cultivate analytical and reflective thinking, and emphasizes the need for comprehensive teacher training and systemic support to optimize critical thinking development.Highlight : Teachers systematically design HOTS-based authentic assessments to improve students’ analytical and evaluative skills. Implementation focuses mainly on cognitive aspects due to challenges in assessing affective and psychomotor domains. Students showed moderate improvement in critical thinking, signaling the need for broader instructional support. Keywords : Authentic Assessment, HOTS, Critical Thinking, Economics Education, Learning Innovation